Political Party as Legal Subject after National Criminal Code - Kolang, Al Rhega Caesar Grestiano; Sukki, A. Tenri; Akram, Muhammad Dinul (Dinasti Research, 2025)
This study seeks to broaden the legal definition of corporations to encompass political parties as entities subject to criminal law. By expanding how we understand corporations in criminal contexts, the research explores whether political parties can be treated as corporate entities that bear criminal responsibility and face prosecution. The proposed criminal penalties for political parties would mirror those applied to corporations under the National Criminal Code, with one notable exception: the potential for dissolution. However, the authority to dissolve political parties remains solely with the Constitutional Court under the 1945 Constitution. The article addresses two primary questions: how political parties should be classified within criminal law frameworks, and what forms of criminal accountability and sentencing should apply to political parties under the new National Criminal Code.